The Effectiveness Of Pre-Donation Water Hydration In Reducing Vasovagal Reaction And Its Risk Factors Among Young Blood Donors In Kelantan - Ismail, Idzham (2019)
Background: Vasovagal Reaction (VVR) is the commonest adverse reaction that occurred among blood donors worldwide. It has negative effect towards donor retention. Therefore it is important to reduce the VVR incidence. The aim of this study was to determine the effectiveness of pre-donation water hydration in reducing VVR among young blood donors in Kelantan. Methods: A quasi experimental study was performed among blood donors in Kelantan who donate blood in blood drives conducted by Transfusion Medicine Unit, Hospital Universiti Sains Malaysia (HUSM) over a period of eight months. A total of 284 young blood donors age from 17 to 23 years old, were assigned equally into two groups, hydration and non hydration group. Donors then were assessed with BDRI 4-Items at 30 minutes and 48 hours post blood donation. Results: The incidence of VVR among young blood donors in this study was 25.4%. Statistically, a hydration group showed significantly lower VVR incidence compared to non hydration group (1.5% vs. 32.5%)(p value = 0.0001). Younger age, lower weight, lower estimated blood volumes were associated with VVR incidence. The mean BDRI score at 30 minutes and at 48 hours were significantly lower in hydration group compared to non hydration group. BDRI 4-Items score at 30 minutes and at 48 hours showed positive correlation only in non hydration group. Conclusions: This study showed that pre-donation water hydration was effective in reducing VVR incidence among young blood donors in Kelantan.